Respuesta :

snog

Answer:

g(3) = -5

Step-by-step explanation:

g(3) is basically the value of g(x) when x = 3. Therefore, g(3) = -3 - 2 = -5.

Answer:

[tex] \boxed{\sf g(3) = -5} [/tex]

Given:

g(x) = -x - 2

To Find:

g(3) i.e. g(x) where x = 3

Step-by-step explanation:

[tex]\sf Evaluate \ -x - 2 \ where \ x = 3:[/tex]

[tex] \sf \implies - x - 2 = - 3 - 2[/tex]

[tex] \sf - 3 - 2 = - (3 + 2) : [/tex]

[tex] \sf \implies - (3 + 2)[/tex]

[tex] \sf 3 + 2 = 5 : [/tex]

[tex] \sf \implies - 5[/tex]